Correction to: Comparative Study to Evaluate Tolerability of Topical 5% Minoxidil Novel Formulation and Alcohol-Based Conventional Solutions in Treatment of Androgenetic Alopecia in Indian Men: Randomized Double-Blind Study - Rashmi Sarkar; Suneel Vartak; Shivani Acharya; Nikhil Kumar Kursam; Amey Mane; Suyog Mehta; Sujeet Narayan Charugulla (Adis, Springer Healthcare, 2020)
In Methods section under Study Design and Patients